Patient Safety Indicators for Judging Hospital Performance: Still Not Ready for Prime Time. (March 2017) - Kubasiak, John C.; Francescatti, Amanda B.; Behal, Raj; Myers, Jonathan A.
Patient Safety Indicators (PSIs) were originally intended for use as a screen for quality of care but are now being used to rank hospitals and to modify hospital reimbursement. PSI data are dependent on accuracy of clinical documentation and coding. Information on whether a PSI event is inherent to the nature of the operation or posed a significant impact on the outcome is lacking. Cases for one year at a single academic center were queried. Cases with target PSIs were included (n = 136). Cases were evaluated for both the inherent nature and significance of injury. Both patient safety officers agreed that the PSI event was inherent to the disease process, and thus, the procedure and was not a marker of patient safety (false positive) in 11.8% to 33.3% of cases. Both reviewers agreed that the events were not clinically significant in 11.8% to 30.4% of cases. This study found high false-positive rates and only moderate interrater reliability for 3 PSIs. PSIs as currently reported are not reliable enough to be utilized for ranking.